2018
DOI: 10.1038/s41386-018-0298-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure, cognition, and brain age in schizophrenia, bipolar disorder, and healthy controls

Abstract: Schizophrenia and bipolar disorder (BD) may be disorders of accelerated aging. Direct comparison of healthy aging populations with schizophrenia and BD patients across the adult lifespan may help inform this theory. In total, 225 individuals (91 healthy controls, 81 schizophrenia, 53 euthymic BD) underwent 3T T1-weighted magnetic resonance imaging, diffusion tensor imaging, and cognitive testing. We analyzed associations among age, diagnosis, and cognition with cortical thickness and fractional anisotropy (FA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
116
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 56 publications
14
116
3
Order By: Relevance
“…These findings are aligned with the range of the brainPAD scores in patients with schizophrenia reported in previous studies (range = 2.6-8 years). 16,[18][19][20][21] However, our finding underscore the importance of algorithm selection given that variation in brainPAD was observed despite all analyses being undertaken on the same dataset.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These findings are aligned with the range of the brainPAD scores in patients with schizophrenia reported in previous studies (range = 2.6-8 years). 16,[18][19][20][21] However, our finding underscore the importance of algorithm selection given that variation in brainPAD was observed despite all analyses being undertaken on the same dataset.…”
Section: Discussionmentioning
confidence: 62%
“…17 Five further brain structural studies have focused on estimating the years of brain-age acceleration in schizophrenia using various machine learning algorithms. 16,[18][19][20][21] Koutsouleris and colleagues used a support vector regression (SVR) algorithm trained on data from 800 healthy individuals, and found that patients with schizophrenia (n=141) had a mean brainPAD of 5.5 years. 18 Schnack and colleagues also used SVR trained on a sample of 386 healthy individuals, and showed that discovery (n=341) and validation sample (n=60) of patients with schizophrenia had a mean brainPAD of 3.8 years and 5.6 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RewP magnitude shows a negative association with age among HC (9), and a depression-focused meta-analysis found that RewP blunting was most pronounced in younger depressed samples (42). Beyond reward processing, growing evidence supports hypotheses of accelerated brain aging in SZ (43)(44)(45)(46)(47), particularly early in the illness course (44,46), which may be due to abnormal brain maturation (48).…”
Section: Introductionmentioning
confidence: 98%
“…SZ has the highest prevalence of all mental illnesses and is very difficult to treat. Over the last few decades, many neuroimaging studies have demonstrated that schizophrenia is a disorder involving widespread abnormalities in the brain structure [1][2][3][4][5]. However, the specific mechanisms involved in producing these structural deficits remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%